Self-Amplifying RNA Vaccine Candidates: Alternative Platforms for mRNA Vaccine Development - Christin Schmidt; Barbara S. Schnierle (Pathogens, 2023)
The present use of mRNA vaccines against COVID-19 has shown for the first time the potential of mRNA vaccines for infectious diseases. Here we will summarize the current knowledge about improved mRNA vaccines, i.e., the self-amplifying mRNA (saRNA) vaccines. This approach may enhance antigen expression by amplification of the antigen-encoding RNA. RNA design, RNA delivery, and the innate immune responses induced by RNA will be reviewed.